Melric and The Sorcerer - McKee, David (Methuen Children's Book Ltd, 1987)
Will triumph over evil, in this latest offering from the creator of Not Now, Bernard? More power, demands the king. But Melric the magician thinks that the king has quite enough power already. A sinister visitor called Sondrak boasts that he can easily grant the king's wish. But when Melric discovers that Sondrak is an evil sorcerer and up to no good a dramatic battle follows.
Keywords: Juvenile literature-Fiction